(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the value of the factor (factors) of "critical thinking" from the main factors in determining the mathematical literacy of students is mathematically substantiated. To find a mathematical justification for the significance of the "critical thinking" factor in improving the mathematical literacy of students, the level of correlation between the two factors was analyzed and, on its basis, the level of regression dependence (correlation coefficient) was tested.